Evaluation of antioxidant, antimicrobial and potential anticancer activities of papaya-based kombucha beverages on colon cancer - Sharifudin, Shaiful Adzni (2024)
Traditional kombucha is prepared by fermenting sugar and tea extract with probiotic microorganisms collectively named as Symbiotic Culture of Bacteria and Yeast (SCOBY). Recently, fruits or leaves juices have become a new, favourable alternative medium for kombucha making. The employment of various starting materials and starter cultures during fermentations might result in the creation of several variable metabolites that may have various bioactivities. Thus, this study was aimed to determine the secondary metabolite content, antioxidant activities, antimicrobial effect against selected food borne pathogens and anticancer activities of the kombucha juices of papaya pulp and leaves fermented using locally isolated kombucha cultures, namely: yeast (Dekkera bruxellensis) and acetic acid producing bacteria (Komagataeibacter rhaeticus).